Growth and Haematological Response of Broiler Chicks Fed Graded Levels of Sweet Potato (Ipomoea batata) Meal as Replacement for Maize - Ayuk, E.A.; Essien, A. (International Journal of Poultry Science, 2009)
The study was conducted to find out the performance and haematological response of broiler birds fed different levels of sweet potato meal (SPM). The levels of sweet potato meal in the different treatment rations were 0, 10, 20, 30, 40 and 50%, respectively. There was a curvilinear decline in growth rate (from 27.9 to 23.3 g/day) as the maize was replaced by sweet potato root meal with a pronounced reduction in performance overall of 17% when all the maize was replaced by sweet potato meal. All haematological parameters assessed only showed minor numerical (P>0.05) differences, falling within the ranges stated in literature. It is concluded that sweet potato root meal can replace maize meal in the diet of broilers over the weight range 50 to 1400 g, with only a slight reduction in growth rate (17% with complete substitution of maize), which may be compensated by the lower cost of the sweet potato meal. The substitution also did not have any deleterious effect on haematological and by extension, the health status of the birds.